Non-standard capitalisation and vocal spelling in intercultural computer-mediated communication. Issue 1 (April 2016) - Lin, Yen-Liang (Eric)
Abstract : This study reports on a corpus analysis of samples of Computer-Mediated Communication (CMC) on an electronic discussion board among a group of British and Taiwanese adolescents, paying specific attention to the most distinctive cues of CMC: non-standard capitalisation and vocal spelling. I evaluate a newly developed corpus of online discussion, the British and Taiwanese Teenage Intercultural Communication Corpus (BATTICC). I used Python programming to calculate all the instances of non-standard capitalisation (specifically, all upper-case words and the use of lower case instead of upper case) and vocal spelling from the corpus, and I also applied Wmatrix to identify the semantic and part-of-speech fields of all these instances. Moreover, initial quantitative analysis was employed to inform further qualitative analysis to identify the pragmatic functions of cues in this intercultural context. It was evident that the CMC cues perform important interpersonal functions, and the analysis demonstrates different preferences by the participants for different purposes.